Acute Postoperative Seizures are a Negative Prognostic Factor for Seizure Freedom After Epilepsy Surgery for Focal Cortical Dysplasia - Rylander, Tyra; Grubor, Irena; Strandberg, Maria Compagno; Bengzon, Johan (World Neurosurgery, 2025)
Background: Focal cortical dysplasia (FCD) is a developmental cortical malformation and a leading cause of drug-resistant epilepsy that often requires epilepsy surgery. Some FCD patients experience acute postoperative seizures (APOS) following surgery. The relationship between APOS and long-term prognosis for patients with FCD is at present unclear. The primary aim of this study was to analyze the association between APOS and postoperative outcomes in patients with FCD who underwent resective epilepsy surgery, as well as to identify factors associated with the occurrence of APOS. Methods: A retrospective registered-based cohort study was performed. Data were obtained from the Swedish National Epilepsy Surgery Registry from 53 patients who underwent resective surgery for FCD between 2014 and 2020. Patients who developed acute seizures occurring within 14 days post-surgery were compared with those who did not. Preoperative and postoperative factors were analyzed to identify predictors of APOS and long-term outcome. Statistical analysis was performed using Fisher exact test, Mann-Whitney U test, and logistic regression. Results: At two-year follow-up, seizure freedom was significantly lower in the APOS group (14.3 % vs. 59%, P = 0.009). APOS was also significantly associated with higher rates of postoperative neurological complications (42.9% vs. 7.7%, P = 0.007). Potential risk factors for APOS included previous neurosurgical operations, particularly reoperations for epilepsy, and parietal and occipital surgeries. Conclusions: APOS is a significant predictor of poor long-term outcome following resective epilepsy surgery for FCD. Previous neurosurgical operations, especially reoperations for epilepsy, and resection within specific brain regions may increase the risk of APOS.
Keywords: Malformations of cortical development; Pharmacoresistent epilepsy; Postoperative complications; Swedish Epilepsy Surgery Registry